Drawing (Out) the Evil (M)other of the Family Court - Davis, Penny (Journal of the Motherhood Initiative for Research and Community Involvement, 2023)
As an artist, PhD researcher, and lone mother to three teenagers, this article introduces a theory of matricentric drawing through an autoethnographic practice of performance drawing. During COVID-19, I turned to my ex-husband to share the care of our children, which backfired with devastating long-term consequences. Rather than softening the blow of the pandemic, the request for help had a slow and destructive effect on our mental health and wellbeing, opening the door for him to remove them from my care. Made in the lead up to the final hearing of a court case in which I risked losing custody of my children, the drawing process began as a reflection upon legal descriptions of myself as an evil (m)other through a textual analysis of the court bundle. The article documents my autoethnographic reflections, as they visualized the effect of legal abuse upon my body and triggered gesture and movements, which were then performed as drawing acts in the family home. With reference to research on single mothers, the impact of COVID-19 and the underlying culture of misogyny, mother blaming, and postseparation legal abuse in the UK family courts, I consider how an autoethnographic approach to my art practice activated drawing as a maternal battle cry, disarming the attacks in legalese and re-armouring my body in preparation for the final hearing. Performed through drawing on the floor and filmed from above within the space of the kitchen, the camera documents the interweaving of daily motherwork with acts of performance drawing. As the drawing evolves, the gestures unfold in synchrony with the authenticity of mother love and care through recorded speech interactions documenting family life. The article considers how matricentric feminism (O’Reilly) informs my arts practice in distinguishing motherhood from mothering as matri-centric drawing enacts an othering of the self. It is useful both in arts-practice research as reflective writing on performance drawing and feminist activism, as data for researchers and policymakers in disentangling the multiple effects on the health and wellbeing of lone mothers and their children during and after the pandemic.